Experimental Study on Mechanical Damage and Fracture Characteristics of Granite under Different Water Cooling Conditions - Zhuangzhuang Yao (Hindawi Limited, 2021)
In order to investigate the mechanical property deterioration and fracture characteristics of granite under different temperature drop and thermal cycle conditions, the evolution laws of mechanical properties, acoustic emission event distribution, and macro and micro failure characteristics of granite under different temperature changes were studied and analyzed by the servo loading, acoustic emission monitoring, and scanning electron microscope systems. The following conclusions were gained from the test results. (1) The peak stress and elasticity modulus of the three temperature drop treatments all decreased with the increase of the number of thermal cycles. In terms of magnitude, the following relationship was satisfied: 10°C > 15°C > 20°C. After 8 cycles, the peak stress and elasticity modulus tended to be stable for 15°C and 20°C temperature drops. (2) At a temperature drop of 20°C, the heterogeneity first increased and then tended to be stable; when the temperature was dropped by 15°C at each cycle, however, the heterogeneity first decreased and then became stable; as for the case of 10°C, the heterogeneity showed an overall decreasing trend. After 4 cycles, the heterogeneities were ranked as 15°C > 20°C > 10°C. After 8 cycles, 20°C > 15°C > 10°C. (3) With the decrease of temperature drop amplitude or the increase of cycles, the connectivity of microcracks in granite improved on the whole, the aperture and shape factor of microcracks increased, the damage of granite intensified, and the duration of the quiet period in the acoustic emission ringing count rate prolonged. (4) The tensile failure dominated at a temperature drop amplitude of 10°C. When the temperature drop was 15°C, the failure mode transitioned from hybrid tension-shear failure to tensile failure as the cycle times increased, whereas the hybrid tension-shear failure dominated with a temperature drop of 20°C.